The COST Action IC1208 Integrating Devices and Materials: A Challenge for New Instrumentation in ICT - Oton, Jose M. (Photonics Letters of Poland, 2017)
The COST Action IDEM celebrated its closing meeting on 16-17 March 2017, nearly four years after its kick-off in May 2013. During this time, the numbers of participant groups and countries has been steadily increasing, from the original 6 countries and 10 groups to the latest numbers, 212 participants belonging to 60 groups of 29 countries. These include most EU countries and several COST and near-neighbor countries such as Turkey, Switzerland, Serbia, Israel, and Russia.